School Quality Improvement: Will Parent Ever Help in Enhancing Effective Educational Inclusive Curriculum Management - Kolik, Abdul (Institut Agama Islam Negeri Lhokseumawe, 2022)
Abstract: The focus of this research is on the collaboration between teachers' roles and parental participation in creating effective learning for children with special needs through an inclusive curriculum. This study is a qualitative field research using a descriptive survey technique. Informants are comprised of school principals, teachers, and several staff members. Informant selection was done using data representatives technique. The results of the study show that (1) efforts by teachers in teaching children with special needs are carried out through understanding the needs of the child, adjusting the learning materials, creating structured lesson plans, utilizing technology, developing social and personal skills of the child, developing vocational skills, evaluating and revising the learning process, and (2) the development of the curriculum for children with special needs involves parental participation by improving communication, creating a conducive learning environment, assisting children with homework, encouraging creative learning activities, and building positive emotional relationships. Abstrak: Fokus penelitian ini pada kolaborasi peran guru dan partisipasi orang tua dalam menciptakan efektivitas pembelajaran anak berkebutuhan khusus melalui kurikulum yang inklusif. Penelitian ini adalah penelitian lapangan berjenis kualitatif dengan teknik survey deskriptif. Informan berasal dari kepala sekolah, guru pengajar, dan beberapa orang staf. Penentuan informan menggunakan teknik keterwakilan data. Hasil penelitian menunjukkan: (1) upaya guru dalam pembelajaran Anak Berkebutuhan Khusus dilakukan dengan cara: memahami kebutuhan anak, menyesuaikan materi pembelajaran, membuat rencana pembelajaran yang terstruktur, menggunakan teknologi, mengembangkan keterampilan sosial dan kepribadian anak, mengembangkan keterampilan vokasional, mengevaluasi dan melakukan pengembangan ulang; (2) pengembangan kurikulum anak berkebutuhan khusus melibatkan partisipasi orang tua dilakukan dengan langkah peningkatan komunikasi, membuat lingkungan belajar yang kondusif, membantu anak dengan tugas-tugas rumah, mendorong kegiatan belajar yang kreatif, dan membangun hubungan emosional yang positif.